Der Reformationstag als gesetzlicher Feiertag und seine fiskalischen Effekte - Michael Broer (Wirtschaftsdienst, 2018)
Die Länder Bremen, Hamburg, Niedersachsen und Schleswig-Holstein haben den Reformationstag ab 2018 als gesetzlichen Feiertag festgelegt; Berlin plant, ebenfalls einen zusätzlichen Feiertag einzuführen. Die Bürger nehmen die Maßnahme positiv auf, die Kosten des Feiertags sind für sie aber nicht sofort zu erfassen. Sie können in höheren Produktionskosten für Unternehmen sowie in geringeren Steuereinnahmen der Bundesländer bestehen. Allerdings werden derzeit über den bundesstaatlichen Finanzausgleich auch die übrigen Länder an den Steuermindereinnahmen beteiligt. Ein Ansatz, um diese Externalisierung der Kosten zu erschweren, bestünde darin, eine Feiertagsbereinigung bzw. -normierung im Länderfinanzausgleich einzuführen. – – In the German system of fiscal equalisation, Länder (states) with below-average tax revenue receive above average payments. The difference between the average and the own tax revenue per capita is compensated up to 63%. To prevent states from getting payments from other states by lowering their own tax rates, tax revenue with taxing autonomy is standardised. States can also influence their tax revenues by changing the number of holidays because each state decides on its own. In 2018, the Bremen, Hamburg, Lower Saxony and Schleswig Holstein introduced designated Reformation Day as a holiday (Berlin also plans to add a holiday). A state with numerous holidays will have lower tax revenues and higher payments in the fiscal equalisation system than the same state with no extra holidays. To consider each state's real ability to pay the fiscal equalisation system, it is necessary to eliminate the effect of differing holidays. This paper shows the fiscal consequence of the new holiday and a way to neutralise this effect and calculates the impact to the states' payments in the fiscal equalisation system.
Keywords: H70; H71; H77; 330